A Review on Application of Solar Energy in Agriculture Sector (International Journal of Innovative Research in Engineering & Management, 2021)
Solar radiation is waste when it falls on the earth in countries  like India. It is predicted that if 1% of the solar radiation  received can be turned into energy, this energy will be  sufficient to satisfy the world's future energy needs. India has  a large agricultural industry that feeds the stomachs of the  majority of the world's people, in addition to solar radiation.  The Indian government has implemented measures to promote  solar energy usage and reduce the use of non-renewable  resources. The current research examines different advances  in the use of solar energy in Indian agriculture, which may be  utilized to reduce electricity consumption from non conventional sources, which are both expensive and  ecologically harmful. According to current study, further  research is needed to improve the applicability and efficiency  of solar power consumption for long-term use.
Keywords: Agriculture; Farmers; India; Renewable; Solar Energy